2017
DOI: 10.1007/s11356-017-8585-5
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Arctic wastewater by chemical coagulation, UV and peracetic acid disinfection

Abstract: Abstract:Conventional wastewater treatment is challenging in the Arctic region due to the cold climate and scattered population. Thus, no wastewater treatment plant exists in Greenland and raw wastewater is discharged directly to nearby waterbodies without treatment. We investigated the efficiency of physicochemical wastewater treatment, in Kangerlussuaq, Greenland. Raw wastewater from Kangerlussuaq was treated by chemical coagulation and UV disinfection. By applying 7.5 mg Al/L polyaluminium chloride (PAX XL1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…The mean reduction values of the faecal indicators at specific PAA doses are reported in Figure 1. During the monitoring, high concentrations [2,28] of faecal coliforms and E. coli, as well as enterococci and C. perfringens were observed in raw sewage ( Table 4). The concentrations of the four bacterial indicators were similar in the summer, autumn, and spring (range: 2.91 to 4.42 log MPN/100 mL or CFU/100 mL), whereas a major contamination was observed during the winter (range: 4.21 to 5.74 log CFU-MPN/100 mL or CFU/100 mL).…”
Section: Salmonella E Coli O157:h7 Campylobactermentioning
confidence: 99%
See 1 more Smart Citation
“…The mean reduction values of the faecal indicators at specific PAA doses are reported in Figure 1. During the monitoring, high concentrations [2,28] of faecal coliforms and E. coli, as well as enterococci and C. perfringens were observed in raw sewage ( Table 4). The concentrations of the four bacterial indicators were similar in the summer, autumn, and spring (range: 2.91 to 4.42 log MPN/100 mL or CFU/100 mL), whereas a major contamination was observed during the winter (range: 4.21 to 5.74 log CFU-MPN/100 mL or CFU/100 mL).…”
Section: Salmonella E Coli O157:h7 Campylobactermentioning
confidence: 99%
“…Several studies have noted that treated and untreated wastewaters are primary contributors of a variety of pathogenic microorganisms, pollutants, and chemicals to the aquatic ecosystem [1,2]. Numerous studies have indicated that primary and secondary wastewater treatment typically achieves 90-99% reductions of enteric microbial numbers.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, an additional conclusive step of effluent disinfection must generally be performed [4,5]. An ideal disinfectant for this step should efficiently remove the pathogenic microorganism's maximum, avoiding the neoproduction of dangerous and undesirable by-products, and should be inexpensive and technologically compatible [6]. The chlorination is the most widely used method for the disinfection of wastewater, because it showed high effectiveness and low residual effect and cost [7].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the phosphate can replace part of the hydroxyl that combines with Fe 3+ . The formation of an alkali-type iron phosphate compound complex can change the hydrolysis paths of Fe 3+ (An et al 2019;Chhetri et al 2018). Iron hydroxide gels and various types of iron oxide could form binuclear complexes after adsorbing a mass of phosphate, which suggests that PO 4 3− can replace two adjacent OH − functional groups and form a bridge between the two Fe 3+ ions.…”
Section: Introductionmentioning
confidence: 99%